Genetic diversity analysis and trait phenotyping for drought tolerance in Amaranth (Amaranthus spp) Germplasm - Jamalluddin, Norain (2020)
Drought is a major abiotic stress which causes severe crop loses worldwide. One way of enhancing food security in areas of limited or unpredictable rainfall is to exploit the wide genetic diversity of underutilised crop species with increased drought tolerance characteristics. This study aimed to develop a precise trait phenotyping strategy for drought tolerance in Amaranthus spp. (Amaranthus tricolor). This research provides a framework to identify the genetic basis of drought tolerance in amaranth germplasm through a panel of 188 amaranth mini core collections.